MAKING DEVELOPMENT PROFESSIONAL LEXICAL COMPETENCE OF MILITARY STUDENTS (Archive of Conferences, 2021)
This article first defines the concept of lexical ability. In addition to emphasizing the importance of lexical ability in military students, measures and important recommendations for the development of professional lexical ability are given